Desain Komersialisasi dan Inovasi Produk Perikanan Olahan Kelompok Usaha di Kawasan Leupung, Aceh Besar - Rahmah, Alvi; Aprilla, Ratna Mutia; Nurfadillah; Agustina, Imelda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The Leupung village of Aceh Besar Regency is famous for its processed salted fish products. The availability of raw materials in the form of fish caught by local fishermen is a promising business opportunity. The community has taken advantage of this opportunity quite well, as seen from the enthusiasm of the community who opened household businesses with processed salted fish products. The community business actors in the Leupung are members of the Samudra Mandiri Syariah Producer Cooperative. The main objective of this community service activity is to improve the economic quality of business groups in the Leupung village, Aceh Besar, with a commercialization design approach and innovation of fishery products. The implementation of the community service has been done in July 2024, with 25 participants. The implementation mechanism for the community service includes counseling to partners, sample quality testing, packaging training, and evaluation of program sustainability. The results of this activity show an increase in the knowledge of fishery business groups regarding the long-lasting shelf life of products, packaging using vacuum and sealer techniques. In conclusion, this community service activity helps partners increase product sales so that partners will obtain optimal profits.